THE EFFECT OF ELECTRONIC FLASHCARD LEARNING MEDIA ON THE ENGLISH VOCABULARY MASTERY OF THIRD GRADE STUDENTS AT SDN TAMANSARI II PULOMERAK - Safira, Meli; Mukhlasin, Mukhlasin; Soraya , Kety (IJOSMAS, 2021)
Vocabulary is the basic element of a language which is used to label things such as adjectives, nouns and verbs to explain the purpose and what was achieved. Not infrequently students find out difficulty to understand English vocabulary. Flashcard media is media that can help in remembering and reviewing lesson materials (Training & Email, 2011). The research was intented to determine the effect of using Flashcard media on the English vocabulary skills of third grade students at SDN Tamansari II Pulomerak. This study used a quantitative approach with a quasi-experimental design method. The results showed (1) the results of the pretest t-count -1,384 > t-table 2,052 or H1 was accepted, namely there were a difference in writing skills between the control class and the experimental class, (2) the results of the posttest t-count -1,528 > t-table 2.052 or H1 was accepted. There were differences in English vocabulary skills between the control class and the experimental class after using Flashcard media. It can be concluded that by Flashcard media students got significant results in English vocabulary skills compared if not using learning media